SMART CITIES’ ENVIRONMENTAL DREAMS AND THEIR DIRTY MATERIAL POLITICS - Kuntsman, Adi (AoIR Selected Papers of Internet Research, 2020)
This paper draws on a study that included two types of materials: firstly, visual and textual analysis of a selection of smart cities’ websites; and secondly, a review of published literature on smart cities and the environment. In both, a celebratory narrative of environmental efficiency prevails. Although ecology is usually not the primary focus of smart cities’ self-promotion, their websites tell a story of how smart cities would ultimately make the environment better, cleaner, and greener. The literature, similarly, talks about “sharing cities”; “green growth”, “green infrastructure”, “progressive urbanisation”, “sustainable urbanism”, “green technology innovation”, “resilient cities”, “smart future” and more. However, despite the overwhelming rhetoric of being environmental saviours, smart cities pose multiple ecological threats, most of which are invisibilised, because they take place elsewhere: the extraction of resources needed to produce the actual devices; the toxicity of their production process and the e-waste left behind; and the rapidly increasing energy demands of data farms, needed to sustain every air pollution sensor, every city dashboard, every smart bus stop, every ‘smart’ communication network. At the heart of my paper lies a troubling, yet crucial question: how to reconcile the rapid and expansive adoption of various smart technologies into environmentally driven initiatives and sustainability projects such as smart cities, with the extensive environmental damages brought on by the digitization itself? How, in other words, can we think about smart cities environmental promises, while taking into account their dirty material politics?